ANALYSIS OF MARKETING POLICY AT THE ZURI HOTEL PALEMBANG - Rizki Allia Septiana; Sulaiman Helmi (SEAN Institute, 2022)
Hotel marketing is an activity that employs a strategy designed to tell a story about the services that a hotel may offer. The purpose of this study was to determine whether marketing practices had an impact on hotel operations. A qualitative case study research method was used. Instruments, interviews, and observations were used. The study's findings indicate that The Zuri Hotel follows the steps in the marketing strategy of paying attention to the current marketing mix, beginning with paying attention to each existing product and establishing pricing based on market scenarios and conditions. Employees and others involved in hotel operations are taught so that their work adheres to business operating requirements. Keep in mind that The Zuri also offers a variety of promos to entice tourists.